If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7y + -5(8x + -2y) = 0 2x + 7y + (8x * -5 + -2y * -5) = 0 2x + 7y + (-40x + 10y) = 0 Reorder the terms: 2x + -40x + 7y + 10y = 0 Combine like terms: 2x + -40x = -38x -38x + 7y + 10y = 0 Combine like terms: 7y + 10y = 17y -38x + 17y = 0 Solving -38x + 17y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17y' to each side of the equation. -38x + 17y + -17y = 0 + -17y Combine like terms: 17y + -17y = 0 -38x + 0 = 0 + -17y -38x = 0 + -17y Remove the zero: -38x = -17y Divide each side by '-38'. x = 0.4473684211y Simplifying x = 0.4473684211y
| 108=3j+3j | | 9x-(7x+5)= | | 7n+n=136 | | s*20=2*5 | | xz+yw=52 | | 3x-2+0.4= | | 4x+2x=66 | | 2x-1=-2 | | 3f+2f+4f= | | 8.9x+17.43=11.1x+17.15 | | 3a+10=4a-6 | | n+2n=15 | | 30x+27=-45x+-8 | | -(4n+2)=-2(2n-1) | | N=20 | | 5a+3a= | | 16x^2-9x+3=0 | | 2(-5)-4y=8 | | 4x+2=6x-3 | | 9.9x+81.36=10.1x+80.42 | | 5n-2=38 | | x+(x+3)=41 | | 24x^2-10x-56=0 | | 2x-3=3x-4 | | n*50=5*2 | | m-6m-7m+4= | | (5w-3)(6w-5)= | | 2u+1.7=4.5 | | 9.1x+99.56=10.9x+98.94 | | 16*13= | | 0.50x+0.05(20-x)=0.10(64) | | 4x^2=7x+36 |